Active ageing and pension system: Finland - Hannu Piekkola; Anni Heikkilä (The Research Institute of the Finnish Economy (ETLA), 2004)
The aim of this paper is to analyse active ageing and retirement in Finland at both the individual worker level and the firm level. The Finnish pension system will undergo some remarkable changes from the year 2005 on: the whole of an individual's working life will determine his or her pension income, there will be higher accruals for postponed retirement as of age 63 with a flexible retirement age of 63-68, and pension levels will be automatically corrected, depending on changes in life expectancy. The desired effect of these new pension rules is that the average retirement age would increase by three years from the current 59 years, but the real labour market effects of the pension reform remain unclear. Based on the interviews that have been conducted, large Finnish firms do not believe that the new pension system will have much effect on the retirement age. Some firms have started to implement their own programmes to improve the longer employability of older workers. The organisations that have experienced large changes and adopted new technology have implemented an active ageing policy more successfully than the others. – – Tässä tutkimuksessa analysoidaan suomalaisten työntekijöiden eläkkeelle siirtymistä ja yritysten eläkestrategioita aktiivisen ikääntymisen näkökulmasta. Suomalainen eläkejärjestelmä tulee uudistumaan vuodesta 2005 alkaen niin, että eläke määräytyy koko työssäoloajan tuloista, kertymäprosentti kasvaa ikävuodesta 63 alkaen eläkkeelle siirtymisen ollessa joustavaa ikävuosina 63-68 ja eläkkeiden tasoa tullaan korjaamaan eliniän odotteen muutosten mukaan. Näiden uudistusten tavoitteena on nostaa keskimääräistä eläkeikää kolmella vuodella nykyisestä 59 vuodesta, mutta todellisia vaikutuksia eläkekäyttäytymiseen ovat vielä vaikeaa ennustaa. Suuret suomalaisyritykset eivät haastattelujen perusteella usko uuden eläkejärjestelmän vaikuttavan eläkeikää nostavasti ja jotkut yritykset ovat käynnistäneet omia aktiivista ikääntymistä tukevia ohjelmiaan. Aktiivisen ikääntymisen ohjelmat ovat onnistuneet parhaiten sellaisissa yrityksissä, jotka ovat läpikäyneet suuria organisaatiomuutoksia ja hyödyntävät uutta teknologiaa.
Keywords: 330; Flexible Altersgrenze; Altenpolitik; Arbeitsethik; Finnland; Alternde Bevölkerung